2012
DOI: 10.1093/carcin/bgs132
|View full text |Cite
|
Sign up to set email alerts
|

PARPs and the DNA damage response

Abstract: Adenosine diphosphate (ADP)-ribosylation is an important posttranslational modification catalyzed by a variety of enzymes, including poly (ADP ribose) polymerases (PARPs), which use nicotinamide adenine dinucleotide (NAD(+)) as a substrate to synthesize and transfer ADP-ribose units to acceptor proteins. The PARP family members possess a variety of structural domains, span a wide range of functions and localize to various cellular compartments. Among the molecular actions attributed to PARPs, their role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 98 publications
2
105
0
3
Order By: Relevance
“…The PARP1-EZH2 axis controls genes involved in cell differentiation; however, our data identify many additional pathways that are regulated by PARP activity, including genes that respond to different insults, such as DNA damage and oxidative stress, and genes involved in the ubiquitination pathway (27,48,49). Although works have shown that PARP is an important mediator in these pathways, our data extend the known contributions of PARP activity to include transcriptional regulation of multiple genes within these pathways, opening an interesting area of research.…”
Section: Discussionmentioning
confidence: 88%
“…The PARP1-EZH2 axis controls genes involved in cell differentiation; however, our data identify many additional pathways that are regulated by PARP activity, including genes that respond to different insults, such as DNA damage and oxidative stress, and genes involved in the ubiquitination pathway (27,48,49). Although works have shown that PARP is an important mediator in these pathways, our data extend the known contributions of PARP activity to include transcriptional regulation of multiple genes within these pathways, opening an interesting area of research.…”
Section: Discussionmentioning
confidence: 88%
“…PARP1 has several effects on different DNA repair pathways and is involved in a variety of distinct cellular processes. 36 To further validate the role of the alt-NHEJ pathway in the context of oncogenic KRAS, we transduced Nomo-1 cells with lentiviral vectors expressing a tet-on-inducible miR-shRNA directed against Lig3a. Treatment with doxycycline resulted in almost complete suppression of Lig3a expression ( Figure 5C).…”
Section: G13dmentioning
confidence: 99%
“…In BRCA-deficient breast cancer, small molecular inhibitors of the DNA-dependent nuclear enzyme poly(ADP-ribose) polymerase (PARP) lead to synthetic lethality and are the subject of ongoing preclinical and clinical investigation as radiosensitizers and adjuvant therapies [7,16,17]. PARP-1plays a pivotal role in the DDR, and also modulates angiogenesis, metastasis, metabolism, survival, chromatin structure, and NF-κB-mediated tumor inflammation [9,10,18,19]. In particular, PARP-1 interacts with NF-κB independent of DNA binding or PARP-1 enzymatic activity to regulate signaling through the TME by activating fibronectin (FN1) and intercellular adhesion molecule 1 (ICAM-1) transcription [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%